(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article we touched upon the place and significance of the works of Muhammad Yusuf, who left a bright mark in the poetry of modern Uzbek literature, and Iqbal Mirza, who is creating today, in the modern literary process. The awareness of the feeling of the Motherland and the reflection of this feeling in the verses of our poets are analyzed.